Питома площа поверхні, кристалітний розмір та термокінетика формування нанопорошків оксиду γ → α-Al2O3 при 570 -1470 К - Гарбуз, В. В.; Петрова, В. А.; Сілінська, Т. А.; Лобунець, Т. Ф.; Биков, О. І.; Муратов, В. Б.; Терентьєва, Т. М.; Кузьменко, Л. М.; Васільєв, О. О.; Оліфан, О. І.; Хомко, Т. В. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2020)
Powders where the γ≈α-Al2O3-nano phases are the priority precursors for catalysts for heterogeneous catalysis with the maximum content of surface 5-coordinated Al centers for Pt attachment. Hydrogenated nano powders (~8 nm) of γ-, γ '-, θ-, κ-Al2O3 soluble in hydrochloric acid were obtained from the processing of aluminum boride powders with an icosahedral structure. Samples, which underwent a step-by-step and single heating of 50-100K heat treatment for 2 hours at temperatures of 570-1470K, were received in quantity of 34. The specific surface area of SВET, m2g-1 was measured by the thermal nitrogen desorption express method of gas chromatography through the GC-1 device. X-ray (phase and coherent), fluorescence and phase chemical-analytical evaluation of the samples were performed. The thermokinetic characteristics of the processes are calculated using the exponential Arrhenius law. Dimensional characteristics of crystallites (10.4-48 nm); specific surface area of powders (213-8.6 m2g-1, SВET); thermokinetic parameters of α-Al2O3 crystallite growth process (V α-Al2O3 - 1.44 10-3 - 6.67 10-3 nm s-1; E α-Al2O3 = 38.7±2.1kJ mol-1; A0 = 0.16±0.0 s-1 along the temperature line 1220-1470K were determined and calculated. The process of dehydration of two OH-groups occurs in the region 570-720K Ea H2O ↑ = 30.5 ± 0.5 kJ mol-1 A0 = 1.33±0.3 s-1. The last group of OH at temperatures of 820 -1070К and a rate of 2.13 10-4 - 4.93 10-4 mol s-1 Ea H2O ↑ = 13.2 ± 0.8 kJ mol-1 A0 = 16.9 ± 0.9 s-1. The activation energy of the phase transition is Ea., γ → α-Al2O3 = 23.9 ± 1.0 kJ mol-1 A0 = 2.01 ± 0.72 s-1 (770-970K) and Ea., γ → α-Al2O3 = 83.5 ± 0.8 kJ mol-1 A0 =(2,05±0,95) 103 s-1 (1070-1170K). It agrees well with the known heat of conversion Eа, γ→α-Al2O3 = 85 kJ mol-1. The TK of γ≈α-Al2O3-nano phases is at 1170K.